2022
DOI: 10.1073/pnas.2118979119
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging intrinsic flexibility to engineer enhanced enzyme catalytic activity

Abstract: Significance Protein flexibility has been recognized as a key contributor to enzyme evolution and catalytic activity. Several studies have illustrated how amino acid substitutions that affect protein flexibility can impact catalysis. However, it is unknown whether structural information regarding conformational flexibility can be exploited for directed evolution of enzymes with higher catalytic activity. Using as a model human kynureninase, an enzyme with important therapeutic implications in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…84 On the other hand, mutations further from the binding site can have ever smaller e ects, 85,86 enabling ne-tuning of mechanics (Fig. 3), [87][88][89][90][91][92] and structure. 93,94 For example, in a separate recent study of ours, we studied the e ect of single mutations on structure (using proteins in the protein data bank, and AlphaFold), nding that structural perturbations are felt up to 2 nm away from the mutated residue.…”
Section: Discussionmentioning
confidence: 99%
“…84 On the other hand, mutations further from the binding site can have ever smaller e ects, 85,86 enabling ne-tuning of mechanics (Fig. 3), [87][88][89][90][91][92] and structure. 93,94 For example, in a separate recent study of ours, we studied the e ect of single mutations on structure (using proteins in the protein data bank, and AlphaFold), nding that structural perturbations are felt up to 2 nm away from the mutated residue.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been observed that the mutagenesis of residues located at flexible regions remote from the active center could also significantly improve the enzyme catalytic efficiency. Recently, such a method was applied to engineer Homo sapiens kynureninase (HsKYNase) for increasing its catalytic activity towards a non-preferred substrate, L-kynurenine (KYN) ( Karamitros et al, 2022 ). B-factor analysis, hydrogen-deuterium exchange coupled to mass spectrometry (HDX-MS) and MD simulations were first applied to predict the highly flexible regions distal to the active center ( Figures 5A–C – C ).…”
Section: Rational Design Strategy Based On Dynamics Modificationmentioning
confidence: 99%
“…Further analysis by HDX-MS and MD simulations revealed that the distal mutations in BF-HsKYNase allosterically influenced the flexibility of the cofactor pyridoxal-5′-phosphate (PLP) binding pocket. This probably altered the conformational ensemble and led to sampling states more favorable to the catalyzed reaction, thereby affecting the reaction rate ( Karamitros et al, 2022 ). Additionally, a conformational dynamics-guided loop engineering strategy was employed to improve activity of an alcohol dehydrogenase from Thermoanaerobacter brockii (TbSADH) towards a non-native substrate ( Liu et al, 2019 ).…”
Section: Rational Design Strategy Based On Dynamics Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Georgiou and colleagues have increased the activity of Homo sapiens KYNase 45-fold by mutagenesis of residues in flexible regions distal to the active site. 199 Scientists at Codexis have also made breakthroughs in the development of an engineered phenylalanine lyase (CDX-6114) that is tolerant to the low pH conditions of the stomach and resistant to intestinal proteases, making it an oral enzyme candidate for the potential treatment of phenylketonuria (NCT04085666). In addition, enzymes with novel activities have been created through protein engineering.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%